Organic Substances From Natural Raw Materials Ordinary Eteries of Cellulouse Are Composited Prospects for the Use of Them On A Wide Range As Raw Materials and Finished Products - M.Murodov; K.B.Karimova; B.B.Akhrarov; N.R. Yakubova (Central Asian Journal of Theoretical and Applied Science, 2022)
Paulownia is a genus of fast-growing trees. Homeland Paulownia - South and Southeast Asia. This tree is very common in Japan and Central China (Paulownia in China is grown on 2.5 million hectares!). All species of Paulownia are fast-growing trees. It is known that Paulownia Feltosa maintains temperatures down to -27 ° C, Elongata variety maintains temperatures up to 16 ° C, and Fortunei variety does not tolerate temperatures below 0 ° C